EVOLUSI PERUBAHAN GARIS PANTAI SETELAH PEMASANGAN BANGUNAN PANTAI - Senjaya Efendi, Soni; Sila Dharma, IG. B.; Suputra, I Ketut (JURNAL SPEKTRAN; Vol. 3, No. 1, Januari 2015, 2015)
Abstract : Reducing the negative effect of erosion problem efforts either by hard structure (e.g. groin construction) or soft structure (e.g. Sand nourishment) solution have been already implemented. One of the location with sand nourishment solution as well as the groin construction is located in Sanur beach, Bali. This location is in critical situation, where the infrastructure is threatened by the lack of the sediment amount and hence it will be impact on the tourism. The evaluation of the coast line changing impact due to the existing of coastal structure need to be assessed. In the worst case, where the coastline changes significantly, the efforts to solve the erosion problems are by groin shape modification and adding the new coastal structure. Simulation results show that there are three segment of the coastal area in between the groin need to be overcome, GN.4 – G7, G39 – GA2 and G32 – G37. The methodology in this study is by comparing the simulation result with the measurement data in 2012.  The evolution of coastline changing in those areas shows significant coastal recesion compare to the other places. What can be done to solve the problem is that by modifying and construct new structure. In GN.4 – G.7, we can construct breakwater paralel to the coastline in the middle. In GN 4, transforming the groin shape from T to I, in the location of G39 – GA2 we propose to omit the bending of the groin in GA2 and construct the groin parallel to the beach in between G39-GA2, in the location of G32 - G37 the breakwaters need to be constructed in the right side and in the left side of the groin G32. The modification of groin construction in the GN.4 – G7, G39 – GA2, and G32 – G37 reduces the losing of material. The coastal recession can be reduced from 6.15 m to 5.34 m in GN.4, in GA 2 from 3.4 m to 2.85 m, and in G32 from 3.69 m to 2.98 m.
Keywords: coastline evolution, Sanur Bali beach, coastline model, groin, breakwater